The British Conservative Party infighting over the formation of European politics (1997–2001) - Matsiushonak, Filip L. (Journal of the Belarusian State University. History, 2018)
Based on the materials of the periodical press and electronic media, the dynamics of inner-party struggle in the Conservative Party of Great Britain about the formation of the European policy in 1997–2010 is considered. The political positions and arguments of the groupings of Eurosceptics and Europhiles are determined. The shift of the official line of the Conservative Party towards Euroscepticism despite the resistance of the supporters of European integration is stated. The negative influence of infighting on the image of the Conservative Party is noted. It is established that excessive concentration of party leadership on the «European issue» has become an obstacle to the renewal of party doctrine, which became one of the main reasons for the defeat in the 2001 general election.